CAGE16-6 Cruise Report: Cruise CAGE16-6 - Bünz, Stefan (CAGE – Centre for Arctic Gas Hydrate, Environment and Climate Report Series, 2023)
The overall goal of cruise CAGE 16-6 is to collect seismic, multibeam and water column data on the W-Svalbard margin and in the outer parts of the Storfjord Trough. The objectives associated with the overall goal are to better understand the occurrence of gas hydrates and fluid leakage, the source of the gas in these systems, and seafloor expressions of fluid seepage. In order to address these objectives we plan to carry out: P-Cable 3D seismic acquisition over gas hydrate and fluid flow areas with potential abiogenic gas sources;P-Cable 3D seismic acquisition over gas-hydrated pingo structures in the Storfjorden Trough;Recovery of 5 OBS stations that were deployed at the Lunde pockmark in October last year for long-term monitoring of microseismicity;Acquisition of additional OBS seismic data to fill gaps in existing data on the eastern segment of the Vestnesa Ridge;2D multi-channel seismic for reconnaissance and stratigraphic correlation;Multibeam mapping to fill in gaps and improve resolution of existing data using the upgraded EM302 system on R/V Helmer Hanssen;Water column mapping of gas flaring on the Vestnesa Ridge using the upgraded EM302 system on R/V Helmer Hanssen The cruise may be known as: CAGE16_6